2021
DOI: 10.1097/jcma.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Association of multiple preventive therapies postdischarge and long-term health outcomes after acute myocardial infarction

Abstract: Background: Statins, beta-blockers, and angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers have been advocated by guidelines as secondary prevention medications to improve the long-term outcomes of post-acute myocardial infarction (AMI) patients. However, adequate drug adherence has always been challenging, and different treatment regimens may lead to divergent outcomes that remain unclear under current myocardial infarction (MI) care standards. This study investigated the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…While differential rates of smoking are an attractive explanation for increased mortality in the US and Taiwan, data from the Global Burden of Disease Study group and OECD suggest relatively modest smoking rates in the US compared with the other IHSRC countries, though smoking rates in Taiwan are fairly high, particularly among men 4647. While large international comparative studies of secondary prevention strategies are limited, data are not clear and convincing that use of statins, angiotensin converting enzyme inhibitors, and β blockers are markedly lower in the US and Taiwan48495051 than countries with lower mortality 852. While it is possible that poorer outcomes in the US and Taiwan can be attributable to social determinants of health, such a supposition requires rigorous evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…While differential rates of smoking are an attractive explanation for increased mortality in the US and Taiwan, data from the Global Burden of Disease Study group and OECD suggest relatively modest smoking rates in the US compared with the other IHSRC countries, though smoking rates in Taiwan are fairly high, particularly among men 4647. While large international comparative studies of secondary prevention strategies are limited, data are not clear and convincing that use of statins, angiotensin converting enzyme inhibitors, and β blockers are markedly lower in the US and Taiwan48495051 than countries with lower mortality 852. While it is possible that poorer outcomes in the US and Taiwan can be attributable to social determinants of health, such a supposition requires rigorous evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The former factor is very important, as assessing drugs prescribed in combination, separately, could lead to overestimation of adherence. The two studies assessing 3 medications altogether: ACEI/ARB, beta-blockers, and statins (although using the traditional PDC or MPR) ( 15 , 16 ), found that 49% and 34% of patients, respectively, adhere to all three therapies ( 15 , 16 ). However, those figures are not directly comparable to our findings, as it does not provide information on adherence behaviors over time.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our results show that increasing adherence to preventive therapies is associated with a significantly decreased risk of mortality in post-AMI patients similar to the previous study ( 10 ). It is important to note that outcomes were assessed during the second year after the index date, which is a common approach ( 15 , 16 ). Therefore, we did not provide information regarding the impact of adherence to recommended therapies in the longer term, which should be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations